PEG-filled kapok fiber/sodium alginate aerogel loaded phase change composite material with high thermal conductivity and excellent shape stability. (April 2021) - Zhang, Qiang; Chen, Bing; Wu, Kun; Nan, Bingfei; Lu, Maoping; Lu, Mangeng
Highlights: Kapok fiber is a natural fiber, cheap and environmentally friendly. Hollow structure and gel structure maintain good shape stability during phase transition. Significantly improve the thermal conductivity while having little effect on the enthalpy change. Abstract: Phase change materials (PCMs) need to improve thermal conductivity and maintain stability to meet actual application requirements. Here, a novel composite based on hydroxylated boron nitride (BN-OH) as a thermally conductive filler with superior thermal energy storage and shape stability is reported. By combining kapok fiber (KF) and sodium alginate (SA), lightweight KF/SA aerogels were fabricated, and their highly porous but durable three-dimensional networks benefit the encapsulation of polyethylene glycol (PEG) and prevent the leakage of PEG. PCMs are prepared by vacuum-assisted impregnating of PEG into the aerogels. The thermal conductivity of 0.684 W∙m −1 ∙K −1 at 10 wt% BN-OH is greatly improved because hydroxyl groups cannot only reduce interfacial thermal resistance but form secure thermal conductive networks. In addition, this novel PCMs possesses excellent shape stability and high latent heat of fusion, and the PCMs keep their shapes stable without any leakage even is compressed upon the melting point of PEG.